(untitled) (Baghdad Science Journal, 2023)
Using sodium4-((4,5-diphenyl-imidazol-2-yl)diazenyl)-3-hydroxynaphthalene-1-sulfonate (SDPIHN) as a chromogenic reagent in presence of non-ionic surfactant (Triton x-100) to estimate the chromium(III) ion if the wavelength of this reagent 463 nm to form a dark greenish-brown complex in wavelength 586 nm at pH=10,the complex was stable for longer than 24 hours. Beer’s low, molar absorptivity 0.244×104L.mol-1.cm-1, and Sandal’s sensitivity 0.021 µg/cm2 are all observed in the concentration range 1-11 µg/mL. The limits of detection (LOD) and limit of quantification (LOQ), respectively, were 0.117 µg/mL and 0.385µg/mL. (mole ratio technique, job’s method) were employed to investigate the stoichiometry of complexes, and both methods revealed that the metal to reagent ratio is equal 1:3.The absorption impact value of the reagent concentration, surfactant concentration, pH, reaction duration, temperature, addition sequences, ionic strength, masking agent, and the influence of many parameters such as affect cations and anions, among others. The influence of temperature on the reaction, which was referred to as an exothermic reaction, was also taken into account while calculating thermodynamic functions. Researchers investigated some of the complex solid’s physical properties, such as solubility, molar conductivity, and melting point, as part of its development. UV-visible rays were used to investigate the chromium complex, while Relative Standard Deviation (RSD%) and Relative Error (E %) were used to assess the precision and accuracy of the novel method.